Innovation for development (United Nations, ECLAC, 2022)
Science, innovation, knowledge and digital technologies have played a fundamental role in the growth potential, social inclusion and environmental sustainability of countries in recent decades, and have become even more important in the context of the crisis caused by the coronavirus disease (COVID-19) pandemic.While Latin American and Caribbean countries have adopted various measures —many of them based on access to technology— to tackle the effects of the pandemic, the region’s structural challenges have become more pronounced, and the need for more comprehensive, complex, participatory and capable innovations systems more evident. This document identifies the areas where efforts should be focused to make progress towards new, more inclusive and sustainable development strategies in which science, technology and innovation are key players for a transformative recovery. Foreword .– Main messages .– Chapter I. A brief overview of science, technology and innovation in Latin America and the Caribbean .– Chapter II. Using science and innovation to revitalize the health industry in Latin America and the Caribbean .– Chapter III. Digital technologies for development .– Chapter IV. Harnessing technology and innovation for more sustainable production.
11362/47795
Keywords: Graue Literatur; Konferenzschrift; Amtliche Publikation; economic growth; inclusive development; innovation; productivity; structural change; sustainable development; economic development; science and technology; innovations; industrial development; health; pharmaceutical industry; medical equipment; digital technology; knowledge-based economy; sustainable production; DESARROLLO ECONOMICO; CIENCIA Y TECNOLOGIA; INNOVACIONES; DESARROLLO INDUSTRIAL; SALUD; INDUSTRIA FARMACEUTICA; EQUIPO MEDICO; COVID-19; TECNOLOGIA DIGITAL; ECONOMIA BASADA EN EL CONOCIMIENTO; PRODUCCION SOSTENIBLE; ECONOMIC DEVELOPMENT; SCIENCE AND TECHNOLOGY; INNOVATIONS; INDUSTRIAL DEVELOPMENT; HEALTH; PHARMACEUTICAL INDUSTRY; MEDICAL EQUIPMENT; DIGITAL TECHNOLOGY; KNOWLEDGE-BASED ECONOMY; SUSTAINABLE PRODUCTION